Perancangan Dan Implementasi E-Jurnal Pada Unit Penelitian Dan Pengabdian Masyarakat (UP2M) STMIK Prabumulih - Ahmat Josi (STMIK Pelita NUsantara, 2017)
E-Journals are electronic journals are serial publications such as the printed form, but this journal is made into an electronic form. It consists of three formats, namely text, text and graphics, as well as full image (in PDF format) publishing process ranging from an announcement of writing requests, author submissions, reviews, notice of review, delivery of writing improvements, editing and layout, printing to every distribution done online by utilizing information technology. The background of electronic journals is the high cost of journal printing, the advancement of computer technology and the widespread of web network technology. One of the managers of E-journals is the research unit and community service (UP2M) Stmik Prabumulih. Currently, UP2M Stmik Prabumulih has published several journals but not published online, so it cannot be accessed by the public, therefore, required a system that can manage electronic journals or often referred to as E-Journal.